Synergistic effects triggered by simultaneous Toll‐like receptor‐2 and ‐3 activation in human periodontal ligament stem cells. Issue 10 (29th May 2019) - Blufstein, Alice; Behm, Christian; Gahn, Johannes; Uitz, Oksana; Naumovska, Ivana; Moritz, Andreas; Rausch‐Fan, Xiaohui; Andrukhov, Oleh
Abstract: Background: Although periodontitis is associated with disruption of the host‐microbial homeostasis, viruses are currently discussed to influence disease progression. Viral pathogens are recognized by Toll‐like receptor (TLR)‐3, which engages a different signaling pathway than other TLRs. This study aimed to investigate the effect of TLR‐3 agonist polyinosinic:polycytidylic acid (Poly I:C) on the expression of inflammatory markers and bone metabolism proteins by human periodontal ligament stem cells (hPDLSCs) compared with TLR‐2 agonist Pam3CSK4, which mimics the effect of bacterial lipoproteins. To assess potential combined effects of bacterial and viral infections, hPDLSCs response to simultaneous TLR‐2 and TLR‐3 activation was investigated. Methods: HPDLSCs were stimulated with Poly I:C (0.0001‐1 µg/mL), Pam3CSK4 (1 µg/mL), and their combinations for 24 hours. Gene expression and protein levels of interleukin (IL)‐6, IL‐8, monocyte chemoattractant protein (MCP)‐1, and osteoprotegerin (OPG) were measured with qPCR and ELISA. Results: Production of IL‐6, IL‐8, MCP‐1, and OPG was significantly increased by Poly I:C or Pam3CSK4 to a similar extent. The levels of all inflammatory mediators induced by simultaneous stimulation with Poly I:C and Pam3CSK4 were significantly higher compared with single stimuli as well as to their summed response. Gene expression and protein levels of OPG were enhanced by Poly I:C, but by lesser extent than by Pam3CSK4. OPG levels upon simultaneous stimulation with Pam3CSK4 and Poly I:C were significantly lower compared with Pam3CSK4 stimulation alone. Conclusions: Simultaneous TLR‐2 and TLR‐3 activation synergistically triggers IL‐6, IL‐8, and MCP‐1 production, which was not observed for OPG. These findings suggest that TLR‐3 activation by viral infections might promote periodontitis progression.